A new system for supporting children with autism spectrum disorder based on IoT and P2P technology. (1st January 2014) - Sula, Ardiana; Spaho, Evjola; Matsuo, Keita; Barolli, Leonard; Xhafa, Fatos; Miho, Rozeta
In this paper, we implement and evaluate the performance of a new system based on internet of things (IoT) and P2P technology for supporting learning and improving the quality of life for children with autism spectrum disorder (ASD). Many children with autism are highly interested and motivated by smart devices such as computers and touch screen tablets. These types of assistive technology devices get children with autism to interact, make choices, respond, and tell parents what they are interested, need, think, and maybe even feel. Our proposed system uses JXTA-Overlay platform and SmartBox device to monitor the children and create P2P communication between children, caregivers and therapists. Various visual systems, such as objects, photographs, realistic drawings, line drawings, and written words, can be used with assorted modes of technology, as long as the child can readily comprehend the visual representation. Vocabulary skills, mathematics skills and other life skills can be taught through our proposed system. We evaluated the effect of our system during study sessions of children diagnosed with ASD. The experimental results show that our system supports engaged learning and the SmartBox increases and maintains the concentration of children with ASD during studying.